Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1093/brain/aws170
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes of outcome measures in spinal and bulbar muscular atrophy

Abstract: Spinal and bulbar muscular atrophy is an adult-onset, hereditary motor neuron disease caused by the expansion of a trinucleotide CAG repeat within the gene encoding the androgen receptor. To date, several agents have been shown to prevent or slow disease progression in animal models of this disease. For the translational research of these agents, it is necessary to perform the detailed analysis of natural history with quantitative outcome measures and to establish sensitive and validated disease-specific endpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
71
2
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(85 citation statements)
references
References 51 publications
11
71
2
1
Order By: Relevance
“…There was no significant difference in age between the two groups ( P =  0.16). The characteristics of this study population, including age, CAG repeat length, disease duration, and ALSFRS‐R scores, were similar to those of previous studies 11, 23, 24. Fifty‐three of the 111 SBMA patients reported having subjective dysphagia (Table 1).…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…There was no significant difference in age between the two groups ( P =  0.16). The characteristics of this study population, including age, CAG repeat length, disease duration, and ALSFRS‐R scores, were similar to those of previous studies 11, 23, 24. Fifty‐three of the 111 SBMA patients reported having subjective dysphagia (Table 1).…”
Section: Resultssupporting
confidence: 72%
“…Longitudinal changes in VFSS findings, especially in the presence of pharyngeal residue in SBMA patients, is another major limitation, partly caused by poor reproducibility of VFSS findings 23. In this study, we found that reproducibility of quantitative markers could be improved by measuring multiple swallows and using the average values of three swallows.…”
Section: Discussionmentioning
confidence: 70%
“…A parameter that reflects muscle volume would enable estimation of disease severity. [6][7][8] The serum level of creatinine (Cr) is currently considered to be the most useful blood parameter that reflects the severity of motor dysfunction in spinal and bulbar muscular atrophy 9 ; serum Cr levels were found to be correlated with the ALS Functional Rating Scale-Revised (ALSFRS-R) score in patients with spinal and bulbar muscular atrophy (correlation coefficient = 0.566, P < 0.001). However, because serum Cr almost exclusively originates from the skeletal muscle and its levels are dependent of renal function, we considered that the use of serum Cr levels as an accurate marker in ALS patients might be questioned.…”
Section: Introductionmentioning
confidence: 99%
“…Creatinine, a marker of muscle mass and metabolism, showed significant change over a three-year period [107]. Similarly, urinary 8-hydroxydeoxyguanosine (8-OHdG), a marker of oxidative DNA damage, also showed significant change over a two-year period in SBMA patients [114].…”
Section: Biomarkersmentioning
confidence: 98%
“…Grip strength is a parameter used in different neuromuscular diseases to easily depict muscle weakness progression. Significant changes in grip strength have been observed in a 3-year longitudinal study of SBMA patients [107] but no significant change over a one year period was detected in another study [103]. A recent study evaluated the measure of tongue pressure using an intraoral pressure probe [108].…”
Section: Biomarkersmentioning
confidence: 99%